Fitting accuracy and constraint force measurement of complete-arch implant-supported fixed dental prostheses made from cobalt-chromium and zirconia frameworks based on the all-on-four treatment concept - Horsch, Laura; Kirsch, Cedric; Zenthöfer, Andreas; Rammelsberg, Peter; Richter, Kevin; Rues, Stefan (Materials, 2025)
The aim of this laboratory study was to evaluate the fitting accuracy of complete-arch implant-supported fixed dental prostheses (ISFDPs) and the occu...
Online veröffentlicht am 20. September 2025
Gesehen am 16.01.2026